Analisis Penutupan Lahan Kawasan Hutan Pada Daerah Aliran Sungai Krueng Aceh Pra dan Pasca Tsunami - Mahyuddin Mahyuddin; Sugianto Sugianto; Teuku Alvisyahrin (Jurnal Manajemen Sumberdaya Lahan, 2013)
Forest Land Cover Analysis of Krueng Aceh Watershed in Pre and Post-TsunamiAbstract. The objective of the study is to assess the changes of coverage of forest area, in watershed of Krueng Aceh by using GIS and remote sensing. The method used in classifying the image data is supervised classification, that is by determining the condition of the land coverage prior to its classification by the image. The pre tsunami classification of Landsat 5 image (2001) of the state-owned forest area along the watershed of Krueng Aceh shows that the land is 29375.47 ha (29.50%) of primary forest, 22140.01 ha (22.23%) of secondary forest, 26618.74 ha (26.73%) of shrubs, 21177.60 ha (21.27%) of open land, and 267.83 ha (0.27%) of water bodies. As a comparison, the post tsunami classification (2009) shows that the lands is 27892.378 ha (28.01%) of primary forest, 33537.58 ha (33.68%) of secondary forest, 16662.18 ha (16.73%) of shrubs, 21275.38 ha (21.37%) of open land, and 212.14 ha (0.21%) of water bodies. Based on this observation, the changes in land coverage of the state-owned forest area along the watershed of Krueng Aceh within the period of 2001 - 2009 is as follows: there is a reduction of 1483.10 ha (5.05%) of primary forest and 9956.56 ha (37.40%) of shrubs, while extension occurs to secondary forest and open land in the order of 11397.57 ha (51.48%) and 97.78 ha (0.46%) respectively.Abstrak. Penelitian ini bertujuan untuk mengetahui perubahan tutupan lahan kawasan hutan pada daerah aliran sungai Krueng Aceh dengan menggunakan SIG dan penginderaan jarak jauh. Metode yang digunakan dalam klasifikasi data citra adalah klasifikasi terbimbing dengan terlebih dahulu mengetahui kondisi tutupan lahan sebelum diklasifikasi terhadap citra. Hasil klasifikasi citra Landsat 5 pra tsunami (2001) pada kawasan hutan di DAS Krueng Aceh adalah hutan primer 29.375,47 ha (29,50%), hutan sekunder 22.140,01 ha (22,23%), semak belukar 26.618,74 ha (26,73%), tanah terbuka 21.177,60 ha (21,27%), dan badan air 267,83 ha (0,27%), sedangkan hasil klasifikasi citra Landsat 5 pasca tsunami (2009) adalah hutan primer 27.892,37 ha (28,01%), hutan sekunder yaitu 33.537,58 ha (33,68%), semak belukar 16.662,18 ha (16,73%), tanah terbuka 21.275,38 ha (21,37%), dan badan air yaitu 212,14 ha (0,21%). Perubahan lahan yang terjadi periode tahun 2001-2009 pada kawasan hutan di DAS Krueng Aceh yaitu terjadi pengurangan hutan primer sebesar 1.483,10 ha (5,05%) dan semak belukar sebesar 9.956,56 ha (37,40%), sedangkan penambahan tutupan lahan terjadi pada hutan sekunder sebesar 11.397,57 ha (51,48%) dan tanah terbuka sebesar 97,78 ha (0,46%).